STUDY OF THE ACCURACY OF EQUATIONS OF STATE FOR PREDICTING THE PARAMETERS OF LEAKAGE OF HYDROGEN GAS MIXTURES UNDER THE CONDITIONS OF GAS DISTRIBUTION NETWORKS - Kopachuk, N. V.; Hryhorskyi, S. Ya. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
In order to create a scientifically sound basis for improving the methods of calculating the parameters of the leakage of gas-hydrogen mixtures, a quantitative assessment of the accuracy of the common cubic equations of state was carried out. The adequacy of the Soave-Redlich-Kwong (SRK) and Peng-Robinson (PR) models for determining the physical properties of mixtures under conditions corresponding to the operation of gas distribution networks was investigated. Multivariate thermodynamic modeling of the compressibility factor, adiabatic index and sound speed was carried out in the PVTsim Nova software package. The study was performed for ten different component compositions of natural gas, taking into account the variability of its composition, with a molar concentration of hydrogen from 0 to 20%. Calculations were carried out in the range of absolute pressures from 0.1 to 1.3 MPa and temperatures from 243.15 K to 323.15 K. The obtained data were compared with the reference results calculated using the fundamental equation of state GERG-2008. It was found that both cubic equations of state provide high accuracy for the studied conditions. It was determined that the average relative error for the SRK equation is: for the compressibility factor – 0.23%, for the adiabatic index – 2.31%, for the speed of sound – 1.11%. For the PR equation, the corresponding errors are 1.04%, 1.61% and 0.76%. The key patterns of the influence of pressure, temperature and hydrogen content on the studied properties are identified and quantitatively described. In particular, it was established with a high degree of approximation reliability that the dependence of the speed of sound on the relative density of the mixture under fixed thermobaric conditions is linear. The results of the study confirm that the common cubic equations of state are a reliable and adequate theoretical basis for the development of new methods for calculating production and technological gas costs.